Internalization of a polysialic acid-binding Escherichia coli bacteriophage into eukaryotic neuroblastoma cells - Timo A. Lehti (Nature Portfolio, 2017)
Eukaryotic organisms are continuously exposed to bacteriophages, but these are not thought to enter non-phagocytic cells. Here, Lehti et al. show that a bacteriophage can bind to a specific receptor on the surface of human neuroblastoma cells in vitro, and be internalized via the endolysosomal route.